2014 Update to the National Seismic Hazard Model in California. (December 2015) - Powers, Peter M.; Field, Edward H.
The 2014 update to the U. S. Geological Survey National Seismic Hazard Model in California introduces a new earthquake rate model and new ground motion models (GMMs) that give rise to numerous changes to seismic hazard throughout the state. The updated earthquake rate model is the third version of the Uniform California Earthquake Rupture Forecast (UCERF3), wherein the rates of all ruptures are determined via a self-consistent inverse methodology. This approach accommodates multifault ruptures and reduces the overprediction of moderate earthquake rates exhibited by the previous model (UCERF2). UCERF3 introduces new faults, changes to slip or moment rates on existing faults, and adaptively smoothed gridded seismicity source models, all of which contribute to significant changes in hazard. New GMMs increase ground motion near large strike-slip faults and reduce hazard over dip-slip faults. The addition of very large strike-slip ruptures and decreased reverse fault rupture rates in UCERF3 further enhances these effects.